The Effect of Employer Branding on Employees Retention, the Mediating Role of Psychological Contract: An Empirical Study on the Employees of International Organizations in Syria - إسماعيل، حسان (جامعة تشرين, 2020)
تهدف هذه الدراسة إلى اختبار تأثير قيم وممارسات سمعة صاحب العمل في الاحتفاظ بالعاملين. جمعت البيانات من المنظمات الدولية العاملة في سورية. تم استخدام الاستبيان كأداة رئيسة في الدراسة، وتم تليل 371 استبيان صالح للتحليل. توصلت الدراسة إلى مجموعة من النتائج، منها: 1.وجود تأثير معنوي وإيجابي للقيم الاقتصادية والنفعية والتطويرية في الاحتفاظ بالعاملين، و وجود تأثير معنوي وسلبي للقيم الاجتماعية في الاحتفاظ بالعاملين، وعدم وجود تأثير معنوي للقيم التطبيقية في الاحتفاظ بالعاملين. 2.وجود تأثير معنوي وإيجابي للقيم الاقتصادية والنفعية والتطويرية في العقد النفسي، وعدم وجود تأثير معنوي للقيم الاجتماعية والتطبيقية في العقد النفسي. 3.وجود تأثير معنوي وإيجابي للعقد النفسي في الاحتفاظ بالعاملين. 4.يؤدي العقد النفسي دور الوساطة الكلية في العلاقة بين ثلاث من قيم سمعة صاحب العمل (الاقتصادية والنفعية والتطويرية) والاحتفاظ بالعاملين، في حين لا يؤدي دور الوساطة بين اثنتين من قيم سمعة صاحب العمل (الاجتماعية والتطبيقية) والاحتفاظ بالعاملين. تم عرض مقترحات وتطبيقات عملية في نهاية الدراسة.
The purpose of this study is to examine the effect of employer branding values and practices on the employees’ retention. Data were collected from both primary and secondary sources. A total number of 371 valid questionnaires were collected from international organizations located in Syria. The main results are: (1) Economic, interest, and developmental values have significant and positive effect on employees’ retention; (2) social value is significant and negative for employees’ retention; (3) and application value is insignificant. (4) Economic, interest, and developmental values are significant and positive for psychological contract; (5) social and application values are insignificant. (6) Psychological contract is positive and significant for retention. (7) Psychological contract fully mediates the relationship between employer branding (economic, interest, and developmental values) and employees’ retention, while it doesn’t play such role for social and application values. Recommendations and practical implications are mentioned at the end of the study.
Keywords: القيادات الإدارية -- الأخلاقيات المهنية -- إدارة الموارد البشرية -- المؤسسات الدولية -- سوريا